Hybrid transverse - longitudinal modes for high figure-of-merit localized plasmonic refractometric sensing in the visible spectrum - Soehartono, Alana Mauluidy (2022)
The nanoscale confinement of plasmonic fields, coupled with their high susceptibility to refractive index changes, makes localized surface plasmons (LSPs) an excellent platform for rapid and label-free sensing. However, the small spatial overlap of the LSP fields with the adsorbed analyte dictates the sensitivity and figure of merit (FOM) of LSP-based sensing. The linear dependence of sensitivity on resonance wavelength, coupled with the dependence of FOM on the achievable resonance Q factor, leads to a sensitivity of ≈100–300 nm per RIU and FOM < 5 for gold-based LSP resonance in the visible range. This presents a dilemma for the realization of a practical sensing platform that requires high sensitivity and high FOM in the visible spectrum. Higher sensitivity and resonance Q factor can be achieved with a larger interaction volume between the plasmonic field and the analyte. This work explores a hybrid mode resulting from an interaction between transverse LSP and longitudinal Fabry–Perot (FP) modes, capable of improving the sensitivity and FOM simultaneously. This hybrid mode is demonstrated in tall v-shaped split ring resonator structures, fabricated via seedless pulsed gold electrodeposition, with FOM of ≈24 in the visible range.